Determination of Seismic Performance Factors for Buildings with Concentrically Braced Frame Systems under the Excitation of Near- and Far-fault Records - Aftabiazar, Mehrdad; Shakeri, Kazem; Salehian, Afsaneh (Periodica Polytechnica Civil Engineering, 2022)
Performance coefficients are widely used in seismic design codes to achieve performance objectives. The values of these coefficients have significant importance in achieving pre-specified performance goals. Studies have shown that near-fault earthquakes decrease the ductility and increase the risk of failure in the structures; however, the current codes use the same performance coefficients to design structures against near- and far-fault records. In the present study, 1-, 5-, 10- and 15-story special concentrically braced frame (SCBF) structures designed in the region with high seismic hazard have been evaluated. Non-linear static, linear dynamic, and incremental non-linear dynamic analyses under the influence of two sets of near- and far-fault records extracted from FEMA-P695 have been used to calculate the performance coefficients. Furthermore, the fragility curves are calculated for three performance levels (IO, LS, CP) using a probabilistic assessment of the results derived from incremental dynamic analysis to investigate the relationship between obtained factors with the probability of exceedance from a specified level. According to the mean results of all records, the behavior factor for the steel special concentrically braced frame is 5.92. The mean behavior factor obtained for the near-fault records is 35% less than the far-fault records. Differences in the obtained behavior factor for structures under excitation of two types of earthquake records (near- and far-fault) are observed in the fragility curves related to the probability of exceedance from CP level. However, there is no significant correlation between the resulted behavior factors and the probability of exceeding IO and LS levels.